Simulação e Análise de Congestionamento em Redes Veiculares - de Brito, Mariana; Tostes, Anna Izabel; Duarte-Figueiredo, Fátima (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
Vehicular congestion is a problem in urban centers. Vehicular network management allows through communication between vehicles and infrastructure the congestion detection and the information dissemination to help drivers changing their route to a less congested one. This paper describes a congestion detection method and compares it with one from the literature. Simulations with real traffic data from Belo Horizonte were performed. The results show that the method described in this paper presents reductions of up to 17% on the mean time for the vehicles to detect congestion.